Black cultural capital : activism that spurred African American high schools - Garry, Vanessa; Isaac-Savage, E. Paulette; Williams, Sha-Lai L. (Emerald Publishing Limited : Information Age Publishing Inc., 2023)
"In antebellum America, Black children, even those of tax-paying Blacks in most states could not attend White public schools or in some states any schools. Nevertheless, with the signing of the Emancipation Proclamation in 1863, Blacks assumed they would receive all inalienable rights granted to them as American freedmen. For most, the right to a proper public education for their children was paramount. Nevertheless, White educators often neglected or poorly implemented Black schools, especially secondary schools. With their reluctance to provide schools for Blacks, African American communities organized and petitioned school districts to develop Black schools on par with those for Whites. In the book, Black Cultural Capital: Activism that Spurred African American High Schools, authors describe the role of the Black community in the development of high schools. Their narratives reveal White educators' unwillingness to implement state laws requiring the education of all children. Their lack of engagement galvanized Blacks to petition boards to adhere to the law. Additionally, they forced school districts to hire Black teachers and provide facilities for Black children equal to those of White children. The fruits of their labor enabled Black children to attend suitable facilities, as well as learn from Black teachers who attended outstanding White and Black colleges and universities. Furthermore, stories of the high schools illustrate how communities sprouted up around them during their heydays as well as, for some, their demise as laws and court decisions eradicated Jim Crow and enabled all Americans to live and learn where they desired"-- Provided by publisher.
Keywords: African Americans -- Education (Secondary); Education, Secondary -- Social aspects -- United States.; Social justice and education -- United States.; African American teachers and the community -- United States.; African Americans -- Social conditions.; Racism in education -- United States.; Discrimination in education -- United States.; Racism -- United States.; United States -- Race relations.; Education -- Philosophy, Theory & Social Aspects.; Relating to African American, Black American people.; Philosophy and theory of education.; elektronické knihy; electronic books